Strong genetic structure among coral populations within a conservation priority region, the Bird's Head Seascape (Papua, Indonesia) - Craig John Starger; Mark van Nydeck Erdmann; Abdul Hamid A. Toha; Andrew Charles Baker; Paul Henry Barber (Frontiers of Biogeography, 2015)
Marine Protected Areas (MPAs) are widely considered to be one of the best strategies available for protecting species diversity and ecosystem processes in marine environments. While data on connectivity and genetic structure of marine populations are critical to designing appropriately sized and spaced networks of MPAs, such data are rarely available. This study examines genetic structure in reef-building corals from Papua and West Papua, Indonesia, one of the most biodiverse and least disturbed coral reef regions in the world. We focused on two common reef-building corals, Pocillopora damicornis (Linnaeus 1758) and Seriatopora hystrix (family: Pocilloporidae), from three regions under different management regimes: Teluk Cenderawasih, Raja Ampat, and southwest Papua. Analyses of molecular variance, assignment tests, and genetical bandwidth mapping based on microsatellite variation revealed significant genetic structure in both species, although there were no clear regional filters to gene flow among regions. Overall, P. damicornis populations were less structured (FST = 0.139, p < 0.00001) than S. hystrix (FST = 0.357, p < 0.00001). Despite occurring in one of the most pristine marine habitats in Indonesia, populations of both species showed evidence of recent declines. Furthermore, exclusion of individual populations from connectivity analyses resulted in marked increases in self-recruitment. Maintaining connectivity within and among regions of Eastern Indonesia will require coral conservation on the local scales and regional networks of MPAs.